Tattoos and Grief: Narratives of Adults from the City of Talca, Chile - Cifuentes-Muñoz, Alejandro (2025)
Grief is a frequent, subjective, and painful experience that arises from the loss of something or someone significant. In such a context, tattoos have become a useful means of confronting such human suffering. This research aims to analyze the narratives of the process involved in getting a tattoo in the context of grief in adults from the city of Talca, Chile. To achieve this objective, qualitative research with a hermeneutic-phenomenological approach was carried out through semi-structured interviews with ten adult women. The data was processed through qualitative content analysis with emerging categorization. The results were grouped into four large narratives: (1) motivations for getting a tattoo, (2) symbolic meanings associated with the process, (3) the therapeutic role of the tattoo, and (4) the consequences of getting a tattoo. It was concluded that the motivation for getting a tattoo was mainly due to previous tattooing experiences and the nature of the bond with the deceased. In addition, tattooing fulfilled a therapeutic function, allowing coping with and processing the loss, and facilitating emotional release at the time of tattooing.